2017
DOI: 10.3390/ijms18061115
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine Flt3-Ligand in Normal and Malignant Hematopoiesis

Abstract: The cytokine Fms-like tyrosine kinase 3 ligand (FL) is an important regulator of hematopoiesis. Its receptor, Flt3, is expressed on myeloid, lymphoid and dendritic cell progenitors and is considered an important growth and differentiation factor for several hematopoietic lineages. Activating mutations of Flt3 are frequently found in acute myeloid leukemia (AML) patients and associated with a poor clinical prognosis. In the present review we provide an overview of our current knowledge on the role of FL in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 177 publications
(220 reference statements)
3
88
1
Order By: Relevance
“…[12][13][14] In patients with acute myeloid leukaemia (AML), FLT3 is frequently mutated and is thus associated with poor prognosis and reduced survival of patients. 9,18 A newly discovered dual FLT3 inhibitor, gilteritinib (ASP2215), 19 remarkably decreases the ability of FLT3positive leukaemia cells to colonize. 17 When FLT3-ITD is expressed in cell line that is factor-dependent, they result in factor-independent growth and malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] In patients with acute myeloid leukaemia (AML), FLT3 is frequently mutated and is thus associated with poor prognosis and reduced survival of patients. 9,18 A newly discovered dual FLT3 inhibitor, gilteritinib (ASP2215), 19 remarkably decreases the ability of FLT3positive leukaemia cells to colonize. 17 When FLT3-ITD is expressed in cell line that is factor-dependent, they result in factor-independent growth and malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…17 When FLT3-ITD is expressed in cell line that is factor-dependent, they result in factor-independent growth and malignant transformation. 9,18 A newly discovered dual FLT3 inhibitor, gilteritinib (ASP2215), 19 remarkably decreases the ability of FLT3positive leukaemia cells to colonize. 20 Gilteritinib reduces the extent of FLT3 phosphorylation and its downstream targets in animal models as well as in cell cultures 21 without any obvious toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoid‐primed multipotent progenitors (LMPPs) express the highest levels of FLT3 (Adolfsson et al , ), and FLT3 plays a key role in LMPP and CLP maintenance (Sitnicka et al , , ). As recently highlighted (Tsapogas et al , ), because no Flt3 conditional knockout mouse has been generated, it remains unclear to what degree the reductions observed in B lymphocyte and thymocyte progenitors in mice with germ line deletion of FLT3 or FLT3L (Mackarehtschian et al , ; Sitnicka et al , , ), are secondary to loss of LMPPs and/or CLPs prior to becoming programmed for lymphoid‐restricted development, or also reflect a distinct role of FLT3 also in already lymphoid‐restricted progenitors. In fact, the expression of FLT3 in the B‐ and T‐lymphocyte lineages, is restricted to the earliest pre‐proB and early thymic progenitors (ETPs), respectively (Wasserman et al , ; Mansson et al , ; Luc et al , ), progenitors suggested largely to represent not fully lymphoid‐restricted progenitors (Rumfelt et al , ; Luc et al , ).…”
mentioning
confidence: 99%
“…Its ligand, FLT3 ligand (FLT3L) exists in a soluble as well as membrane-bound form (Lyman et al, 1995;Lyman & Jacobsen, 1998). Studies in mice have established that FLT3 and FLT3L play an important role in lymphopoiesis (Lyman & Jacobsen, 1998;McKenna et al, 2000;Sitnicka et al, 2002;Tsapogas et al, 2017). Although not expressed on haematopoietic stem cells (HSCs), FLT3 expression is initiated on multipotent progenitors (MPPs) and sustained on common lymphoid progenitors (CLPs), but is only expressed on the very earliest B-cell and T-cell progenitors (Wasserman et al, 1995;Adolfsson et al, 2001Adolfsson et al, , 2005Sitnicka et al, 2002;Boyer et al, 2011;Buza-Vidas et al, 2011;Luc et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation